The Baltic and Arabic Character of the Sovius Tale. The Origins of the Mythonym - Lemeškin, Ilja (Tautosakos darbai, 2015)
The object of the article is the tale of Sovius, the origins of which (whether oral or written – translated) still inspire heated debates. The mythic personal name Sovius should be regarded as an artificial construction, and its appearance attributed to a mistaken deciphering of the copied original, as result of which the first syllable of the possessive adjective  was interpreted as the aorist of the verb ‘to be’, while the rest of the adjective – as a name:   >    >   . The name of questionable authenticity is not part the folkloric narrative itself, since it is found before and after the etiological legend, i.e. in the portions of text where the literary intentions of the author are expressed.Functioning of such a “name” is determined by the euhemerism of the written monument of the 1262. The first sentence    is a continuation of the literary title: *            “The tale of the pagan fallacy, this Sovius is called god, [although] Sovius was a man”. The deductive conclusion follows: Sovius is called god – Sovius was a man → man is called god. The hitherto established statement that folklore piece starts with words    “Sovius was a man” is bound to be corrected. The beginning of the etiological tale should reasonably be related to the following fragment of text:     “when he caught the wild boar…”Discussions of the possible written sources are lacking in argumentation based on textual analysis, since there is considerable shortage of the written artefacts that could be paralleled to the Sovius tale in terms of their narrative structure and semantics. Folklorists possess such textual parallels in their store – primarily, the Lithuanian tale “Rooms in Heaven” (AT 802*). The oral nature of the narrative in question is supported by the chronograph itself. The title of its 18th chapter *         “The tale of the pagan fallacy, this Sovius is called god” contains an important indication of the genre  “something that exists orally, that is told”. The notion  lays and obligation on the modern researchers to use and consider primarily this authentic denomination.
Keywords: -